Dynamic Spillovers of Economic Policy Uncertainty: A TVP-VAR Analysis of Latin American and Global EPU Indices - Nini Johana Marín-Rodríguez; Juan David González-Ruíz; Sergio Botero (Economies, 2025)
This study examines the dynamic interconnectedness of economic policy uncertainty (EPU) among Latin American economies—Brazil, Chile, Colombia, and Mexico—and significant international regions, including the United States, Europe, and Japan, as well as a global EPU index. Using a Time-Varying Parameter Vector Autoregressive (TVP-VAR) model with monthly data, this study reveals the evolving spillover effects and dependencies capturing how uncertainty in one market can transmit across others on both regional and global scales. The findings highlight the significant impact of external EPU, particularly from the U.S. and global EPU sources on Latin America, positioning it as a primary recipient of international uncertainty. These results underscore the need for Latin American economies to adopt resilience strategies—such as trade diversification and regional cooperation—to mitigate vulnerabilities to global shocks. This study offers valuable insights into the mechanisms of economic uncertainty transmission, guiding policymakers in developing coordinated responses to reduce the effects of external volatility and foster regional economic stability.